2022
DOI: 10.1111/plb.13415
|View full text |Cite
|
Sign up to set email alerts
|

The role of species interactions for forest resilience to drought

Abstract: Increasing durations and frequencies of droughts under climate change endanger the sustainable functioning of forests worldwide. The admixture of species with complementary resource use may increase the resilience of forests towards drought; however, little is known about modifications of species interactions (i.e. facilitation and competition) by increasing drought severity in mixed forests. In particular, knowledge on the regulation of central ecohydrological processes, such as tree water fluxes, is lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 93 publications
2
26
0
Order By: Relevance
“…1A; Jansen et al, 2021), we did not detect an overall decrease in δ 13 C with NSR and thus no general enhancement of water availability in more diverse tree neighbourhoods. Similarly to our finding, other studies found mixed results and no universal decrease in δ 13 C in mixtures compared to monocultures (Grossiord, 2020; Haberstroh & Werner, 2022). Jansen et al (2021) found the strongest relationship between NSR and δ 13 C for trees with high a high degree of crown competition from neighbours and only marginal effects for trees with low crown competition.…”
Section: Discussionsupporting
confidence: 87%
“…1A; Jansen et al, 2021), we did not detect an overall decrease in δ 13 C with NSR and thus no general enhancement of water availability in more diverse tree neighbourhoods. Similarly to our finding, other studies found mixed results and no universal decrease in δ 13 C in mixtures compared to monocultures (Grossiord, 2020; Haberstroh & Werner, 2022). Jansen et al (2021) found the strongest relationship between NSR and δ 13 C for trees with high a high degree of crown competition from neighbours and only marginal effects for trees with low crown competition.…”
Section: Discussionsupporting
confidence: 87%
“…After 2018, P. sylvestris mortality most likely induced a competition release for understorey trees, which can lead to a higher understorey productivity in the growing period (Cavin et al . 2013; Ogaya & Peñuelas 2021; Haberstroh & Werner 2022). Thus, the growth of the understorey explained the recovery of NDVI in 2019 and 2020, as well as the partial recovery of summertime NEE and GPP in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Grossiord et al (2015) reported negative impacts of plant–plant interactions on water fluxes for Pinus sylvestris , but positive effects for Quercus faginea and Pinus nigra . Thus, plant–plant interactions can buffer or amplify drought stress for co‐existing plants (Grossiord, 2020; Haberstroh & Werner, 2022). Therefore, it is likely that plant competition or facilitation trigger modifications of the plants' hydraulic strategy in comparable ways to abiotic factors.…”
Section: Introductionmentioning
confidence: 99%